The Implementation of STEM- and AI-Based Project-Based Learning in Enhancing Problem-Solving Skills and Self-Regulated Learning of Elementary School Students - Made Ayu Pransisca; Samsul Hadi; Tika Winda (Journal of Educational Studies, 2025)
This study aims to examine the effectiveness of implementing Project-Based Learning (PjBL) integrated with Science, Technology, Engineering, and Mathematics (STEM) and Artificial Intelligence (AI) in enhancing problem-solving skills and self-regulated learning (SRL) among elementary school students. The study was motivated by the low level of students' problem-solving skills and SRL, which has largely been attributed to the persistence of teacher-centered instruction. A mixed-methods approach was employed using a quasi-experimental design with a non-equivalent control group. The participants were fifth-grade elementary school students assigned to an experimental group and a control group. Data were collected through tests, questionnaires, observations, and interviews, and were analyzed using normality tests, homogeneity tests, independent samples t-tests, and thematic analysis. The findings indicate that STEM- and AI-based PjBL significantly enhances students' problem-solving skills and SRL.